Gul e lala panchvi jamat k lia - Ahsaan,Fouzia Farooqi (Karachi: Oxford university press, 2024)
The Oxford Gul-e-Lala series, specifically the Class 5 book, is an educational resource used in Pakistan, designed to meet the academic standards set for students in the fifth grade. This book typically focuses on enhancing students' proficiency in Urdu through various short stories, poetry, and essays. The texts are designed to improve reading comprehension, vocabulary, and grammar, while also connecting students to Pakistan's literary and cultural heritage.
Keywords: Gul e lala- textbook